2015
DOI: 10.1155/2015/408096
|View full text |Cite
|
Sign up to set email alerts
|

Association of theNOTCH4Gene Polymorphism rs204993 with Schizophrenia in the Chinese Han Population

Abstract: NOTCH4 regulates signaling pathways associated with neuronal maturation, a process involved in the development and patterning of the central nervous system. The NOTCH4 gene has also been identified as a possible susceptibility gene for schizophrenia (SCZ). The objective of this study was to examine the relationship between NOTCH4 polymorphisms and SCZ in the Chinese Han population. The rs2071287 and rs204993 polymorphisms of the NOTCH4 gene were analyzed in 443 patients with SCZ and 628 controls of Han Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
(29 reference statements)
3
8
3
Order By: Relevance
“…Table 1 presented the demographic, genetic, and behavioral data for participants included in the final analysis. The genotype distribution of NOTCH4 rs204993 in current study (AA = 142, AG = 188, and GG = 72) was consistent with the previous report of variation of this gene in healthy Chinese Han population (Zhang et al, 2015a). There were no significant differences in gender, educational years and age between genotype groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Table 1 presented the demographic, genetic, and behavioral data for participants included in the final analysis. The genotype distribution of NOTCH4 rs204993 in current study (AA = 142, AG = 188, and GG = 72) was consistent with the previous report of variation of this gene in healthy Chinese Han population (Zhang et al, 2015a). There were no significant differences in gender, educational years and age between genotype groups.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, study among 218 Taiwanese families has found another SNP, rs204993 with significant relationship with schizophrenia through testing the association of the entire genomic region of NOTCH4 (Liu et al, 2007). Specially, the AA genotype of rs204993 was associated with a higher risk for schizophrenia in the Chinese Han population (Zhang et al, 2015a). As the intermediary role of brain function for the genetic effect on schizophrenia, there may be significant differences of brain function in schizophrenia-related region between distinct genotypes of rs204993.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the demographic, genetic, and behavioral data for participants included in the final analysis. The genotype distribution of NOTCH4 rs204993 in the current study (AA = 142, AG = 188, and GG = 72) was consistent with a previous report of variations of this gene in the healthy Chinese Han population [16]. Genotype groups did not significantly deviate from Hardy-Weinberg equilibrium (χ2 = 0.505, p = 0.477).…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that we found that the FCS of the occipital cortex was degressive in sequences of the GG, AG, and AA genotype groups that suggest an additive effect of rs204993. This is not in complete agreement with a recessive effect revealed by the previous results that the AA genotype of rs204993 is associated with a higher risk for schizophrenia in the Chinese Han population [16]. The difference between schizophrenia and schizotypal traits may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation